2021
DOI: 10.1080/22221751.2021.1885999
|View full text |Cite
|
Sign up to set email alerts
|

Amoebae can promote the survival of Francisella species in the aquatic environment

Abstract: Francisella tularensis, a tier 1 select agent, is the causative bacterium of tularemia, a zoonosis with a large animal reservoir. However, F. tularensis, like many other Francisella species (including F. novicida and F. philomiragia), is assumed to have an aquatic reservoir. The mechanisms of Francisella species persistence in surface water remain poorly characterized. In this study, we deeply investigated the long-term interactions of the tularemia agent F. tularensis subsp. holarctica, F. novicida or F. phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Furthermore, using this isolate ( Fth A-271), we corroborate earlier findings showing that the culturability of Francisella over time in water is improved at lower (4°C) temperatures rather than at higher ones (RT, 22.5°C). Furthermore, using the amoeba Naegleria gruberi we here can confirm prior publications, demonstrating that Francisella is not able to multiply in amoebae ( Acanthamoeba castellanii , A. polyphaga , Vermamoeba vermiformis ) ( Buse et al, 2017 ; Hennebique et al, 2021 ). However, lower temperatures and the presence of amoeba increased the survival and the long-term culturability of the bacterium ( Abd et al, 2003 ; El-Etr et al, 2009 ; Duodu and Colquhoun, 2010 ; Verhoeven et al, 2010 ; Gilbert and Rose, 2012 ; Ozanic et al, 2016 ; Buse et al, 2017 ; Golovliov et al, 2021 ; Hennebique et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, using this isolate ( Fth A-271), we corroborate earlier findings showing that the culturability of Francisella over time in water is improved at lower (4°C) temperatures rather than at higher ones (RT, 22.5°C). Furthermore, using the amoeba Naegleria gruberi we here can confirm prior publications, demonstrating that Francisella is not able to multiply in amoebae ( Acanthamoeba castellanii , A. polyphaga , Vermamoeba vermiformis ) ( Buse et al, 2017 ; Hennebique et al, 2021 ). However, lower temperatures and the presence of amoeba increased the survival and the long-term culturability of the bacterium ( Abd et al, 2003 ; El-Etr et al, 2009 ; Duodu and Colquhoun, 2010 ; Verhoeven et al, 2010 ; Gilbert and Rose, 2012 ; Ozanic et al, 2016 ; Buse et al, 2017 ; Golovliov et al, 2021 ; Hennebique et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, using the amoeba Naegleria gruberi we here can confirm prior publications, demonstrating that Francisella is not able to multiply in amoebae (Acanthamoeba castellanii, A. polyphaga, Vermamoeba vermiformis) (Buse et al, 2017;Hennebique et al, 2021). However, lower temperatures and the presence of amoeba increased the survival and the long-term culturability of the bacterium (Abd et al, 2003;El-Etr et al, 2009;Duodu and Colquhoun, 2010;Verhoeven et al, 2010;Gilbert and Rose, 2012;Ozanic et al, 2016;Buse et al, 2017;Golovliov et al, 2021;Hennebique et al, 2021). Therefore, we chose Fth A-271 WT strain to investigate its ability to form biofilms and to colonize and survive in a natural aquatic multispecies biofilm.…”
Section: Discussionsupporting
confidence: 88%
“…pneumophila, as well as numerous other bacteria, have shown the ability to enter and multiply in A. castellanii cells [16]. A recent study also showed that amoebae likely promote survival of some bacteria in aquatic environments [62]. After the life cycle in an amoeba, L. pneumophila becomes more resistant to destruction by pasteurization treatment compared to agar-grown bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the DNA detection of the tularemia agent does not allow us to determine the detected bacteria’s infectivity. Several in vitro experimental studies have shown that F. tularensis can survive in water through interaction with amebae [ 30 , 31 , 32 , 33 ]. Acanthamoeba species were especially shown to promote Francisella sp.…”
Section: Discussionmentioning
confidence: 99%